Pengaruh Sharia Conformity dan Good Governance Business Sharia terhadap Kinerja Bank Umum Syariah - Ismail Suleman; Imran Rosman Hambali; Ronald Soemitro Badu (Jambura Accounting Review, 2021)
This research aims to examine the influence of Islamic Investment, Islamic Income, Profit sharing, implementation of duties and responsibilities of the Sharia Supervisory Board (SSB), and implementation of duties and responsibilities of the Director towards the performance of Sharia Commercial Bank. The data in this research are obtained by downloading the annual financial report of each sharia bank for the period 2014-2018 (5 years), the selected sample was 6 banks, so the number of observations was 30. The findings indicate that partially, the variable of Sharia Conformity as measured by the indicators of Islamic investment and Islamic income has no influence on the performance of Sharia Commercial Bank where indicator of profit sharing influence the performance of Sharia Commercial Bank. Meanwhile, the variable of Good Governance Business Sharia as measured by indicators of the implementation of duties and responsibilities of SSB and indicators of implementation of duties and responsibilities of the Directors have an influence on the performance of Sharia Commercial Bank. The variable of Sharia Conformity and Good Governance Business Sharia are able to explain the performance of variable of Sharia Commercial Bank of 29%.